PIM1 signaling in immunoinflammatory diseases: an emerging therapeutic target - Yang, Xue; Liu, Chunming; Lei, Yuxi; Liu, Zhi; Zhu, Bin; Zhao, Dongchi (Frontiers in Immunology, 2024)
PIM1, the proviral integration site for Moloney murine leukaemia virus, is a member of the serine/threonine protein kinase family. It is involved in many biological events, such as cell survival, cell cycle progression, cell proliferation, and cell migration, and has been widely studied in malignant diseases.However, recent studies have shown that PIM1 plays a prominent role in immunoinflammatory diseases, including autoimmune uveitis, inflammatory bowel disease, asthma, and rheumatoid arthritis. PIM1 can function in inflammatory signal transduction by phosphorylating multiple inflammatory protein substrates and mediating macrophage activation and T lymphocyte cell specification, thus participating in the development of multiple immunoinflammatory diseases. Moreover, the inhibition of PIM1 has been demonstrated to ameliorate certain immunoinflammatory disorders. Based on these studies, we suggest PIM1 as a potential therapeutic target for immunoinflammatory diseases and a valid candidate for future research.Herein, for the first time, we provide a detailed review that focuses on the roles of PIM1 in the pathogenesis of immunoinflammatory diseases.